The Effect of Transformational Leadership, Organizational Culture, and Work Life Balance on Employee Performance - Murniawati, Adita; Achmad, Nur (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to measure how much influence transformational leadership, organizational culture, and work-life balance have on employee performance mediated by organizational commitment. The study was conducted using a purposive sampling method distributed to employees of the Regional Finance Agency of Karanganyar Regency with a total of 90 respondents, the data obtained were then analyzed using partial least square with SmartPLs and then it was found that transformational leadership did not have a significant effect on employee performance or organizational commitment, and did not have a significant effect on employee performance when mediated by organizational commitment. However, organizational culture has a positive and significant effect on employee performance and organizational commitment, and also has a significant effect on employee performance when mediated by organizational commitment. While work-life balance has a positive effect on employee performance and organizational commitment, but is not significant on employee performance alone or when mediated by organizational commitment. Organizational commitment itself has a positive and significant effect on employee performance.